The Influence of Emotional Value and Value for Money on Repurchase Intention of Gofood Users in The Distric Tanjung Morawa - Fahrezi Saragih, Reynaldi; Yunita, Nindya; Khairunnisak, Khairunnisak (Journal of Management and Business Innovations, 2024)
This research aims to examine the influence of emotional value and value for money on repurchase intention among Gofood users in Tanjung Morawa sub-district. This research uses a quantitative type of research, which is tested using the SPSS statistics 23 program. The population in this research is people in Tanjung Morawa sub-district who have made transactions on Gofood 2 or more times and the total population is 227,396 people in Tanjung Morawa sub-district. This research method uses a quantitative method, the research method is one way obtain and seek tentative truth, not absolute truth. Based on the answer obtained from 100 people who use GoFood more than 2 order in tanjung morawa sub district for each statement in the variabel X2 (value for money) which has been tested by researchers in the multiple linear regression test, the partial results (t-test) obtained that value for money has a t-count value of 0.000 < 0.1. Keyword: Emotional Value, GoFood, Repurchase Intention, Value For Money